The students’ coordinating conjunction acquisition order - Deby Irawan (Journal on English as a Foreign Language, 2018)
This study is aimed at uncovering the students’ acquisition order of coordinating conjunction for then to seek the possible causes of such phenomenon. Quantitative approach with implicational scaling and qualitative approach with case study were employed with test, focused-group interview, and document analysis of some related textbooks as the instruments. A test consist of 70 questions about the usage of seven coordinating conjunctions in which each word is represented by 10 questions was given to the 13 students of eleventh grade of senior high school for the data collection related to the students’ acquisition order. The documents were then analyzed through several steps as suggested by the expert. The results show that the students acquire “and”, “so”, “for”, “but”, “or”, “yet”, and “nor” as in order. The external factors which influence the order are the formal complexity of each conjunction and the lack of exposure of coordinating conjunction both in the teaching activity and textbooks. Thus, teachers are suggested to provide more explicit teaching on coordinating conjunction and necessary knowledge about the usage of each word. Also, book writers should provide ample exposure to give students more knowledge about the usage of those conjunctions in a meaningful context.